Die Bibel als moralisches Bilderbuch? Kants ‚doktrinale Hermeneutik‘ und ihr Nutzen für die moralische Kultur des Menschen - Sebastian Abel (Кантовский сборник)
This research aims to present a coherent analysis of so-called “doctrinal hermeneutics” by examining notable passages from Religion within the Bounds of Bare Reason and the Critique of the Power of Judgment. It is first shown that doctrinal hermeneutics essentially relies on symbolic hypotyposis, which can be understood as thinking by analogy supplemented with a reference to intuition. Here, both an historical and a contemporary interpretation inform the reconstruction of what Kant understands by “symbolic hypotyposis”. Further, the specific nature of the ideas that Kant develops in Religion is examined, and it is shown that these are to be classified as ‘impure’ ideas — in contrast to the ‘pure’ ideas dealt with in the second Critique, e.g., of God. With the analogy and the distinction between pure/impure, it is possible to locate the entirety of ideas within a taxonomy. Finally, it is explored the specific purpose of such “symbolic interpretation”, and it is demonstrated that the value in question lies precisely in the ability to bridge the gap between intuition and concepts of pure reason. In this way, we can approach the incomprehensibilities and paradoxes faced by the human being who, while under the authority of the moral law, is nevertheless constituted “naturally”. This type of moral interpretation also positively influences the moral motivation of the interpreter.